2021
DOI: 10.1371/journal.pone.0254127
|View full text |Cite
|
Sign up to set email alerts
|

The role of race and scientific trust on support for COVID-19 social distancing measures in the United States

Abstract: Pundits and academics across disciplines note that the human toll brought forth by the novel coronavirus (COVID-19) pandemic in the United States (U.S.) is fundamentally unequal for communities of color. Standing literature on public health posits that one of the chief predictors of racial disparity in health outcomes is a lack of institutional trust among minority communities. Furthermore, in our own county-level analysis from the U.S., we find that counties with higher percentages of Black and Hispanic resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…Ethno-racial minorities appeared to be more hostile than the majority population to vaccination in general which confirmed studies on the greater reluctance of African Americans in the United States to receive the new vaccine [ 13 ]. Numerous studies have shown that ethno-racial minorities have less confidence in the healthcare system and in caregivers than the majority population [ 30 32 ]. In the case of France, this mistrust can be explained on the one hand by the weight of its colonial history and the associated pharmaceutical scandals [ 33 ], and on the other by discrimination and mistreatment to which these populations may have been exposed when resorting to the public health system [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethno-racial minorities appeared to be more hostile than the majority population to vaccination in general which confirmed studies on the greater reluctance of African Americans in the United States to receive the new vaccine [ 13 ]. Numerous studies have shown that ethno-racial minorities have less confidence in the healthcare system and in caregivers than the majority population [ 30 32 ]. In the case of France, this mistrust can be explained on the one hand by the weight of its colonial history and the associated pharmaceutical scandals [ 33 ], and on the other by discrimination and mistreatment to which these populations may have been exposed when resorting to the public health system [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that ethno-racial minorities have less confidence in the healthcare system and in caregivers than the majority population [ 30 32 ]. In the case of France, this mistrust can be explained on the one hand by the weight of its colonial history and the associated pharmaceutical scandals [ 33 ], and on the other by discrimination and mistreatment to which these populations may have been exposed when resorting to the public health system [ 32 ]. Interestingly, their hostility to the Covid-19 vaccine was less marked than for the vaccine in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, critical health researchers have also problematized traditional framings within vaccine 'acceptance' and 'hesitancy' literatures, emphasizing the role of previously underappreciated factors like trust [23,24]. The example of trust is particularly illustrative of the importance of considering attitudinal and experiential variables (rather than, say, only demographic correlates), as its effect on the uptake of COVID-19 preventive measures can be larger within marginalized and/or non-dominant groups [25][26][27].…”
Section: Reviewing the Literature: The Complexity Of Vaccine Decision-makingmentioning
confidence: 99%
“…Studies in the United States found that trust in government and government sources was associated with adherence to social distancing [ 6 ]. Kazemian et al found in the United States that scientific trust raised support (although adoption was not measured) for Covid-19 social distancing policies [ 7 ]. Expanding this analysis beyond the United States of America (USA), to include Japan, and Hong Kong (HK), and focusing on the self-reported adoption of pandemic control measures including social distancing and mask wearing, and using expanded antecedents, we generate some novel, highly topical, and policy-relevant findings.…”
Section: Introductionmentioning
confidence: 99%